Daily positive events and diurnal cortisol rhythms: Examination of between-person differences and within-person variation - Sin, Nancy L. (Psychoneuroendocrinology, 2017)
Growing evidence from field studies has linked daily stressors to dysregulated patterns of diurnal cortisol. Less is known about whether naturally-occurring positive events in everyday life are associated with diurnal cortisol. The objectives of this study were to evaluate daily positive events as predictors of between-person differences and within-person (day-to-day) variations in diurnal cortisol parameters, in addition to daily positive events as buffers against the associations between daily stressors and cortisol. In the National Study of Daily Experiences, 1,657 adults ages 33–84 (57% female) reported daily experiences during telephone interviews on 8 consecutive evenings. Saliva samples were collected 4 times per day on 4 interview days and assayed for cortisol. Multilevel models were used to estimate associations of daily positive events with cortisol awakening response (CAR), diurnal cortisol slope, and area under the curve (AUC). At the between-person level, people who experienced more frequent positive events exhibited a steeper diurnal cortisol slope, controlling for daily stressors, daily affect, and other covariates. At the within-person level, positive events in the morning (but not prior-night or afternoon/evening events) predicted steeper decline in cortisol across that day; positive events were also marginally associated with lower same-day AUC. Associations were not mediated by daily positive affect, and positive events did not buffer against stressor-related cortisol alterations. These findings indicate that individual differences and day-to-day variations in daily positive events are associated with diurnal cortisol patterns, independent of stressors and affect.